APLIKASI PRINSIP DESAIN UNIVERSAL PADA SEKOLAH INKLUSI TERPADU DI SURAKARTA - Nur Khoiratri Dewi; Agung Kumoro Wahyuwibowo; Ahmad Farkhan (ARSITEKTURA, 2017)
Abstract: Education is a fundamental need that must be owned by all society level. Today’s education development is one of the results from the education quality improvement. One of the ways to improve the quality itself is by applying the inclusive school. As the contribution to facilitate the same chance in education for disable students, the planning and design for Integrated Inclusive School was created. Integrated Inclusive School was designed in one area considering the fact that Surakarta has not owned yet the Inclusive School in one education area with disable students accommodated (such as blind, low vision, deaf, and physical disability students). The related problem to design is how the form of planning and design concept for Integrated Inclusive School in Surakarta. Besides, the concept could hold inclusive education system to accommodate the need of user by applying the universal design principal. The purpose of Integrated Inclusive School is to accommodate the teaching learning process considering the ability and the activity of disable students by applying universal design. The planning and design of Integrated Inclusive School used Universal Design to support ease, safety, and comfort for everyone without discrimination. The concept of Integrated Inclusive School applied principal universal design which includes the space concept, location and site selection, mass and building appearance. The basic form of building was the dominance of a square shape and mass organizing of building was cluster and centralized circulation system. Keywords : Education, inclusive school, integrated system, universal design.